COVID‐19: An Australian center's perspective. Issue 5 (30th October 2020) - Lim, Lisa; Matalanis, George
Abstract: SARS CoV‐2 (COVID 19) is having a deep and lasting impact around the world. We review the effect it has had on our cardiothoracic surgery practice in Australia and give insights into our contingency planning, restructuring, practice changes, and the effect on our patients in this evolving pandemic.